Electrocatalytic degradation of diuron herbicide using three-dimensional carbon felt/β-PbO2 anode as a highly porous electrode: Influencing factors and degradation mechanisms. (August 2021) - Rahmani, Alireza; Seid-mohammadi, Abdolmotaleb; Leili, Mostafa; Shabanloo, Amir; Ansari, Amin; Alizadeh, Saber; Nematollahi, Davood
Abstract: Traditional planar PbO2 anodes have been used extensively for the electrocatalytic degradation process. However, by using porous PbO2 anodes that have a three-dimensional architecture, the efficiency of the process can be significantly upgraded. In the current study, carbon felt (CF) with a highly porous structure and a conventional planar graphite sheet (G) were used as electrode substrate for PbO2 anodes. Both CF/β-PbO2 and G/β-PbO2 anodes were prepared by the anodic deposition method. The main properties of the electrodes were characterized by XRD, EDX-mapping, FESEM, and BET-BJH techniques. The electrocatalytic degradation of diuron using three-dimensional porous CF/β-PbO2 anode was modeled and optimized by a rotatable central composite design. After optimizing the process, the ability of porous CF/β-PbO2 and planar G/β-PbO2 anodes to degrade and mineralize diuron was compared. The electrocatalytic degradation of the diuron was well described by a quadratic model (R 2  > 0.99). Under optimal conditions, the kinetics of diuron removal using CF/β-PbO2 anode was 3 times faster than the G/β-PbO2 anode. The energy consumed for the complete mineralization of diuron using CF/β-PbO2 anode was 2077 kWh kg −1 TOC. However, the G/β-PbO2 anode removed only 65% of the TOC by consuming 54% more energy. The CF/β-PbO2 had more stability (115 vs. 91 h), larger surface area (1.6287 vs. 0.8565 m 2  g −1 ), and higher oxygen evolution potential (1.89 vs. 1.84 V) compared to the G/β-PbO2 . In the proposed pathways for diuron degradation, the aromatic ring and groups of carbonyl, dimethyl urea, and amide were the main targets for HO radical attacks. Graphical abstract: Image 1 Highlights: Electrochemical preparation of highly porous PbO2 anode on carbon felt substrate. The BET area of the carbon felt/ꞵ-PbO2 anode was 2 times larger than that of the graphite/ꞵ-PbO2 . Development of a quadratic model to describe the degradation of diuron with the carbon felt/ꞵ-PbO2 anode. The rate of diuron removal with carbon felt/ꞵ-PbO2 anode was 3 times higher than graphite/ꞵ-PbO2 . Possible pathways were suggested for diuron mineralization.